The Neglected Role of Bile Duct Epithelial Cells in NASH - Cadamuro, Massimiliano; Lasagni, Alberto; Sarcognato, Samantha; Guido, Maria; Fabris, Roberto; Strazzabosco, Mario; Strain, Alastair J.; Simioni, Paolo; Villa, Erica; Fabris, Luca (Seminars in Liver Disease, 2021)
Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide, and affects 25% of the population in Western countries. NAFLD is the hepatic manifestation of the metabolic syndrome, linked to insulin resistance, which is the common pathogenetic mechanism. In approximately 40% of NAFLD patients, steatosis is associated with necro-inflammation and fibrosis, resulting in nonalcoholic steatohepatitis (NASH), a severe condition that may progress to cirrhosis and liver cancer. Although the hepatocyte represents the main target of the disease, involvement of the bile ducts occurs in a subset of patients with NASH, and is characterized by ductular reaction and activation of the progenitor cell compartment, which incites portal fibrosis and disease progression. We aim to dissect the multiple biological effects that adipokines and metabolic alterations exert on cholangiocytes to derive novel information on the mechanisms driven by insulin resistance, which promote fibro-inflammation and carcinogenesis in NASH.
Keywords: nonalcoholic fatty liver disease; insulin resistance; metabolic syndrome; ductular reaction; cholangiocarcinoma